Early Initiation of Breastfeeding for The Pregnant Women - Maimunah. R; Maya Sari; Nopita Yanti Br Sitorus (IJCS: International Journal of Community Service, 2023)
Breast milk is the gold standard of baby food for children, because it will be the first step in fulfilling children’s right. There are many benefits of breastfeeding for babies in carrying out Early Initiation of Breastfeeding and exclusive breastfeeding for mothers and children. One of the benefits is to increase the bond between mother and her child, to increase the baby's immunity, to reduce the incidence of infection in infants, to increase optimal child growth and development, to increase children's intelligence and it is also as a natural contraceptive for mothers. Some research results state that breast milk is also useful in preventing various diseases such as cancer in children, heart disease, and diabetes mellitus. In the current developments of maternal and child health, the program of Management of Early Initiation of Breastfeeding, Exclusive Breast Milk and Lactation Management are increasingly being encouraged. These three programs are related to one another. Breast milk is generally the gold standard of baby food for children, because it will be the first step in fulfilling children's rights.